The cultural politics of emotion - Ahmed, Sara, 1969- (Edinburgh : Edinburgh University Press, 2014)
What do emotions do? How do emotions move us or get us stuck? In developing a theory of the cultural politics of emotion, Sara Ahmed focuses on the relationship between emotions, language and bodies. She shows how emotions are named in speech acts, as well as how they involve sensations that are felt by the skin. The Cultural Politics of Emotion develops a new methodology for reading 'the emotionality of texts' and offers analyses of the role of emotions in debates on international terrorism, asylum and migration, and reconciliation and reparation. New for this edition: an extensive Afterword, 'Emotions and Their Objects, ' which situates the book in relation to the emergent field of affect studies, as well as in relation to the author's body of scholarly work. New for this edition. An extensive Afterword, 'Emotions and Their Objects' which situates the book in relation to the emergent field of affect studies, as well as in relation to the author's body of scholarly work; a revised bibliography; updated throughout.
Introduction: Feel your way -- The contingency of pain -- The organisation of hate -- The affective politics of fear -- The performativity of disgust -- Shame before others -- In the name of love -- Queer feelings -- Feminist attachments -- Conclusion: Just emotions -- Afterword: Emotions and their objects.
Includes bibliographical references (pages 234-248) and index.
Online resource; title from digital title page (viewed on December 2, 2020).
JSTOR
Keywords: Emotions -- Social aspects; Language and emotions -- Political aspects; Political psychology; Political culture; Langage et émotions -- Aspect politique; Psychologie politique; POLITICAL SCIENCE -- Essays; POLITICAL SCIENCE -- Government -- General; POLITICAL SCIENCE -- Government -- National; POLITICAL SCIENCE -- Reference; PHILOSOPHY -- History & Surveys -- General; Emotions -- Social aspects; Political culture; Political psychology; Kulturwissenschaften; Gefühl; Politik; Politische Kultur; Politische Psychologie; Känslor.; Politisk psykologi; Politisk kultur; Electronic book